Comparative Statics in Linear Programming and the Giffen Paradox - Beckmann, M. J. (Review of Economic Studies, 1955)
Journal Article Comparative Statics in Linear Programming and the Giffen Paradox Get access M. J. Beckmann M. J. Beckmann New Haven, Conn. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 23, Issue 3, 1955, Pages 232–235, https://doi.org/10.2307/2295728 Published: 01 December 1955